Historical Determinants of Regional Divisions of Georgia and their Implications for Territorial Governance - Mądry, Cezary; Kaczmarek-Khubnaia, Julia (Quaestiones Geographicae, 2016)
Georgia can be characterised by its turbulent history, centuries-old traditions, and a great ethnic diversity. This makes it necessary to include historical determinants, in addition to geopolitical and economic factors, when making a regional analysis of its territory and contemporary governance issues. Five stages of the development of the present territorial division of Georgia are distinguished. They have been identified by means of an analysis of key events (critical junctures) of significance in the formation of its historical regions. Additionally, their influence at each of the three levels of the current territorial division of independent Georgia is discussed, in particular in the context of territorial governance.